ANALISIS METODE CARD SORT DALAM PEMBELAJARAN MUFRADAT BERBASIS PENDEKATAN KOGNITIF - Tamsil, Irvan Maulana (IAIN Batusangkar, Indonesia, 2020)
The purpose of this study is to analyze the using of card sort method in learning Arabic vocabulary based on cognitive approach. In this study, the researcher used was library research. The finding of this study indicated that in the learning Arabic vocabulary based on cognitive learning, teacher provided an opportunity for students to think, understand, and explore because this approach is proses-based, not product-based. Someone’s behaviour is decided by his understanding about situation related to the learning objectives. The learning process supports students to be more active (student-centered). In this case, the teacher as a facilitator used a card sort method in learning process, thus, the students are more enthusiastic and do not feel bored in learning Arabic vocabulary.